Gluten-Free Products for Celiac Susceptible People - Rai, Sweta; Kaur, Amarjeet; Chopra, C. S. (Frontiers in Nutrition, 2018)
The gluten protein of wheat triggers immunological reaction in some gluten sensitive people having HLA-DQ2/8 genotypes, which leads to Celiac disease (CD) with symptomatic damages the small intestinal villi. Glutenin and gliadin are two major components of gluten that are essentially required for developing a strong protein network for providing desired viscoelasticity of dough. Many nongluten cereals/starch (rice, corn, sorghum, millets and potato/pea starch) and various gluten replacers (xanthan and guar gum) have been used for retaining the physic-sensorial properties of gluten-free, cereal-based products. This paper reviews the recent advances in the formulation of cereal-based, gluten-free products by utilizing alternate flours, starches, gums, hydrocolloids, enzymes, novel ingredients and processing techniques. The pseudo cereals, amaranth, quinoa, and buckwheat, are promising in gluten-free diet formulation. Genetically-modified wheat is another promising area of research where successful attempts have been made to silence the gliadin gene of wheat using RNAi techniques. The requirement of quantity and quality gluten-free packaged foods is increasing consistently at faster rate than lactose-free and diabetic foods. More research needs to be focused in cereal-based, gluten-free beverages to provide additional options for CD sufferers.